Location Question Analysis of the Umkm Sector of Jombang District (British Journal of Multidisciplinary and Advanced Studies, 2023)
The existence of MSMEs is an alternative effort to overcome poverty, improving people's living standards through continuous empowerment of MSMEs. The aim of this research is to formulate a Location Quotion analysis strategy model for the MSME sector that can determine superior products to improve community welfare and regional income in Jombang Regency in accordance with superior potential and the problems faced.This research was carried out in several sub-districts in Jombang Regency, namely: Compiling a map of the potential conditions of superior products, revitalizing the development and conceptualization of alternative development opportunities for the MSME sector, and applying the SWOT analysis model, and applying LQ analysis with approaches namely: quantitative and descriptive.The development of small businesses (MSMEs) plays a role in creating economic conditions to form a competitive market mechanism, increasing the impetus for economic growth from domestic economic forces into the process of expanding employment opportunities and forming entrepreneurs evenly. The results of the LQ analysis are developing regional superior commodities, namely rice, sugar cane, duck eggs, beef, free-range chicken meat, broiler meat and fisheries considering that from the results of the LQ analysis these superior commodities have an LQ value> 1.